Edukacyjny potencjał krytycznych wydarzeń życiowych w perspektywie biograficznego uczenia się1 - Skowrońska-Pućka, Agnieszka (Kultura-Społeczeństwo-Edukacja, 2019)
The article contains deliberations on the subject of adult learning as a result of breaking points in people’s lives. It is based on Fritz Schütze and Gerhard Riemann’s concept of the trajectory, trying to show the educational potential of critical life events. The paper constitutes an illustration about learning and biography. The analysis concerns an individual who experienced domestic violence, was separated from her family of origin by being placed in a care and educational institution, whose life was additionally complicated by teenage pregnancy and motherhood. The analysis of the narrative makes it possible to see two dimensions of the relationship between learning and biography – learning from the experiences we face during life and biographical learning (or learning from a biography).